Fecal microbiota transplantation-current perspective on human health - Zixuan Cao; Tingting Gao; Ousman Bajinka; Yali Zhang; Xingxing Yuan (Frontiers in Medicine)
Recently, microbiome medicine has attracted the attention of researchers. While this rapidly growing medical approach for various diseases and disorders is changing the paradigm, it is imperative to weigh both its benefits and the associated risk factors. For instance, manipulation of the gut microbiota (GM) has positive effects on metabolic and neurodegenerative diseases. Notably, fecal microbiota transplantation (FMT), a complex method, has shown promise; however, many doubt its feasibility without adverse effects on human health. Given the number of human clinical trials investigating FMT for the treatment of various disorders, this review summarizes recent findings on its impact on human health. This review summarizes the metabolic responses associated with FMT and their reversal effects on gastrointestinal infections, behavioral changes, and immune responses. Additionally, this review discusses the role of FMT in antimicrobial resistance and its co-supplementation effects on human health, safety, potential risks, limitations, prospects, and recommendations. Although this review does not cover all the studies in the database, the searched terms for FMT and human health in clinical trials are sufficient to provide a summary of the current perspective.